From benzodiazepines to fatty acids and beyond: revisiting the role of ACBP/DBI - Alquier, Thierry; Christian-Hinman, Catherine A.; Alfonso, Julieta; Færgeman, Nils J. (Trends in endocrinology and metabolism, 2021)
Four decades ago Costa and colleagues identified a small, secreted polypeptide in the brain that can displace the benzodiazepine diazepam from the GABAA receptor, and was thus termed diazepam binding inhibitor (DBI). Shortly after, an identical polypeptide was identified in liver by its ability to induce termination of fatty acid synthesis, and was named acyl-CoA binding protein (ACBP). Since then, ACBP/DBI has been studied in parallel without a clear and integrated understanding of its dual roles. The first genetic loss-of-function models have revived the field, allowing targeted approaches to better understand the physiological roles of ACBP/DBI in vivo. We discuss the roles of ACBP/DBI in central and tissue-specific functions in mammals, with an emphasis on metabolism and mechanisms of action.
Gesehen am 14.02.2022